Pengembangan Media Pembelajaran Berbantuan Aplikasi Alight Motion pada Materi Peralatan Dalam Konstruksi Bangunan: Penelitian - Ndruru, Hadirat; Zebua, Yelisman; Telaumbanua, Arisman; Telaumbanua, Aprianus (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to develop a learning medium using Alight Motion for the subject Construction Equipment at SMK Negeri 1 Sogae’adu and to examine its validity, practicality, and effectiveness. The background of this research lies in the limited variety of instructional media used by teachers, which results in low student motivation and difficulties in understanding abstract concepts. The research employed the Research and Development (R&D) method with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The instruments used were validation sheets, response questionnaires, and learning achievement tests. The findings indicate that the developed media was assessed by experts as highly feasible, received positive responses from teachers and students who considered it practical and engaging, and was proven effective in enhancing students’ comprehension and learning achievement. Thus, the Alight Motion-based learning medium can serve as an innovative alternative in digital-based vocational learning at vocational high schools.